Second international workshop on models and processes for the evaluation of off-the-shelf components (MPEC'05). - Chung, Lawrence (Software engineering notes.)
Off-The-Shelf Software components (hereafter OTS) play an increasingly important role in software systems development. One of the central activities in a successful OTS-based system development is OTS evaluation, which is one of the cornerstones of OTS selection, OTS implementation and cost models for OTS. Achieving a better understanding of this activity is the objective of the "International Workshop on Models and Processes for the Evaluation of OTS Components (MPEC)". After the first edition collocated with ICSE'04, a second edition has taken place (May 21th, 2005, Saint Louis, Missouri, USA), again as a satellite event of ICSE.This paper reports on the structure of the workshop, presenting short summaries of the talks given and the research issues identified and heavily discussed during the workshop. More details are available at the workshop URL: http://www.lsi.upc.es/events/mpec.